Effectiveness of the Tier 1 Program of the Project P.A.T.H.S.: Preliminary Objective and Subjective Outcome Evaluation Findings - Daniel T.L. Shek (The Scientific World Journal)
There are two tiers of programs in the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes). In the Tier 1 Program, teaching units based on different positive youth development constructs are covered. Pre- and post-test data utilizing the Chinese Positive Youth Development Scale (CPYDS) and post-test subjective outcome evaluation data were collected from 546 students who participated in the 20h Tier 1 Program of the P.A.T.H.S. Project. Results showed that high proportions of the respondents had positive perceptions of the program and the instructors, with 85.3% of the respondents regarding the program as helpful to them. Positive changes in the program participants in many measures of positive youth development were also observed. Although there were some increases in problem behavior in some areas, adolescent problem behavior was generally stable. The present study provides preliminary support for the effectiveness of the Tier 1 Program of the Project P.A.T.H.S. in Hong Kong.